2019
DOI: 10.1177/0300060519870718
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management and progress in sudden sensorineural hearing loss during pregnancy

Abstract: Sudden sensorineural hearing loss (SSNHL) is a relatively rare, but distressing, disease in pregnant women. Little is known about the causes, clinical manifestations, treatments, and prognosis of SSNHL. Some hypotheses have been proposed to explain the pathophysiological mechanism of SSNHL, but most of them have not been identified. This article reviews the existing literature to present a summary of this clinical problem. Most patients suffer from SSNHL in the second or third trimester, and show moderate to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Moreover, all patients gave birth to healthy neonates with normal Apgar scores, which suggested that intratympanic therapy is safe and tolerable for pregnant women. Other recommended therapies include dextran-40 and hyperbaric oxygen therapy[ 24 ]. Wang and Yang[ 18 ] administered 3.5 L of 10% dextran-40 intravenously to six pregnant patients, achieving a success rate (PTAs < 25 dB or mean hearing gains ≥ 30 dB) of 83.3%[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all patients gave birth to healthy neonates with normal Apgar scores, which suggested that intratympanic therapy is safe and tolerable for pregnant women. Other recommended therapies include dextran-40 and hyperbaric oxygen therapy[ 24 ]. Wang and Yang[ 18 ] administered 3.5 L of 10% dextran-40 intravenously to six pregnant patients, achieving a success rate (PTAs < 25 dB or mean hearing gains ≥ 30 dB) of 83.3%[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal changes in the endolymphatic fluid may alter the homeostasis and enzymatic processes at the cochlea, stria vascularis, spiral ligament, and spiral ganglion neurons, as well as at the afferent terminations of neurons. Moreover, estrogen affects some enzymatic receptors at the sodium-potassium channels throughout the cochlea and membranous labyrinth leading to the presentation of otologic symptoms in pregnant patients [ 16 - 19 ]. Other events described in relation to the inner ear include the fluid retention in endolymph and perilymph and hypercoagulability in the auditory arteries.…”
Section: Reviewmentioning
confidence: 99%
“…The labyrinth vascularization is caused by the labyrinthine artery and its branches [ 16 - 19 ]. These are highly vulnerable to vascular occlusion [ 16 - 19 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations